Comparative Regulation of E-Commerce Contracts and Consumer Protection in Indonesia and Thailand - Pebriani, Rosi; Nurhilmiyah (Al-Risalah, 2026)
The development of electronic commerce (e-commerce) has significantly changed the pattern of buying and selling transactions and has given rise to complex legal implications, particularly regarding the validity of agreements, consumer protection, and dispute resolution mechanisms. This article aims to analyze and compare the legal regulations for online buying and selling in Indonesia and Thailand, as well as to examine efforts to resolve legal issues arising in e-commerce transaction practices in both countries. This research uses a normative legal research method with a statutory and comparative approach. Data were obtained through a literature review of relevant laws and regulations, legal doctrines, and scientific literature. The results of the study indicate that online buying and selling transactions in Indonesia and Thailand are both recognized as valid legal acts as long as they meet the requirements for valid agreements and electronic contract provisions. Indonesia regulates e-commerce through specific sectoral regulations, namely the Electronic Information and Transactions Law and Government Regulation Number 80 of 2019 concerning Commerce Through Electronic Systems, while Thailand integrates e-commerce regulations into the Civil and Commercial Code, the Electronic Transactions Act, and the Consumer Protection Act with a strong emphasis on consumer protection. In dispute resolution, both countries prioritize non-litigation mechanisms, but differ in the role of dominant actors. Indonesia emphasizes the role of e-commerce platforms and the Financial and Transaction Supervisory Agency (BPSK), while Thailand demonstrates more active state involvement. From an Islamic legal perspective, online buying and selling is, in principle, permitted as long as it meets the pillars and conditions of sale and is free from elements of usury, gharar, and fraud. This study emphasizes the importance of strengthening regulations, effective implementation, and increasing digital legal literacy to ensure legal certainty and consumer protection in e-commerce transactions.